The impact of culture on trust and purchase intention in social commerce shopping behaviour - Esterhuizen, Joanne (School of Management Studies, 2019)
Social commerce has evolved through the advancement of web 2.0 technologies, the significant rise of smartphone usage, and the increased popularity of social media platform usage such as social networking sites. Social networking sites have unique social sharing capabilities, which enable consumers to research products and services and make informed shopping decisions based on the trust developed in their online community. Brands acknowledge the importance of building and gaining consumer trust, because trust is a significant determinant for successful online transactions. Trust is equally essential to social commerce success, and is established as a positive influence on purchase intention. Considering the impact of trust on the consumer decision-making journey online, how this trust develops and what moderates this trust are of equal significance to brands and academics. Despite the plentiful research conducted in social commerce, the moderating role of culture on trust in social commerce is questioned, and the uncertainties of its impact within an emerging country is evident through insufficient academic research. The research design used in this study was cross-sectional in nature. Quantitative data were collected from a sample of social commerce users though an online survey administered on a branded Facebook page. Adopting an integrative social commerce framework by Kim and Park (2013) and the national cultural framework of Hofstede, the findings demonstrated a positive relationship between trust and purchase intention, and no moderation of culture on trust. Reinforcing previous academic research on the significance of trust in social commerce – further recommendation is given on the exploration of culture on trust and purchase intention.